2020
DOI: 10.1155/2020/6396274
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Lemierre’s Syndrome Presented with Multifocal Pneumonia and Cerebral Venous Sinus Thrombosis

Abstract: A 27-year-old female patient initially presented with fever, myalgia, sore throat that progressed to multifocal pneumonia, and cerebral sinus venous thrombosis. A combination of upper respiratory symptoms with tooth infection, positive blood culture for Fusobacterium nucleatum, computed tomography (CT) chest finding of multifocal pneumonia, and magnetic resonance imaging (MRI) finding of internal jugular vein thrombosis (IJVT) and cerebral venous sinus thrombosis (CVST) suggested Lemierre syndrome. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Tis perspective is also refected in the only retro-perspective study available that studied about 700 cases of LS from 2000 to 2017 and concluded that there are no disease-specifc elements of concern regarding the safety of anticoagulation in LS [12]. From our analysis of 26 LS cases from 2016 to 2021, anticoagulation was used in 76% of cases and the average duration was 9.8 weeks (ranging from 1 week to 16 weeks; Table 2 [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44]. In our case, due to the absence…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis perspective is also refected in the only retro-perspective study available that studied about 700 cases of LS from 2000 to 2017 and concluded that there are no disease-specifc elements of concern regarding the safety of anticoagulation in LS [12]. From our analysis of 26 LS cases from 2016 to 2021, anticoagulation was used in 76% of cases and the average duration was 9.8 weeks (ranging from 1 week to 16 weeks; Table 2 [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][41][42][43][44]. In our case, due to the absence…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the duration of antibiotics, Riordan, 2007, referenced an estimate of 9 to 84 days with an average of 42 days [2]. We have analyzed 26 cases of LS from 2016 to 2021, and the average antibiotics duration was 5.3 weeks (Table 2) [4,17,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][42][43][44]. In clinical practice, due to the lack of an established guideline, the duration and selection of antibiotics highly varied based on clinical responses in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lemierre’s Syndrome (LS) is a triad of oropharyngeal infection, thrombosis of internal jugular vein and bacteremia due to F. necrophorum (commonest anaerobe) but other aerobic pathogens like E. coli , Staphylococcus and Streptococcus have also been implicated as causative agents 1 …”
Section: Discussionmentioning
confidence: 99%
“…2 In pharyngitis this pathogen penetrates through the oropharyngeal tissue to the vascular structures and leads to thrombosis, thrombophlebitis, septic emboli, and metastasis. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation